2019
DOI: 10.1177/1847979019827149
|View full text |Cite
|
Sign up to set email alerts
|

Examining psychological capital of optimism, self-efficacy and self-monitoring as predictors of attitude towards organizational change

Abstract: This study ascertains whether three positive organizational behaviour capacities (optimism, self-efficacy and self-monitoring) predict attitude towards organizational change. Design of this study was cross-sectional, and data were collected with self-report measure. One hundred sixty-nine employees were drawn from 21 organizations in Delta State, Nigeria. The participants were made of 108 (64%) females and 61 (36%) males, with the mean age of 40.21 years (SD, 9.13). Simple regression analysis revealed that opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 63 publications
7
40
0
6
Order By: Relevance
“…We provide evidence that the relationship between psychological capital and internal learning is mediated by the perceived team structure. This confirms that one of the distinctive features of psychological capital, and one that has an important practical contribution to make, is its openness to change and development (Choi & Lee, 2014;Han, Brooks, Kakabadse, Peng, & Zhu, 2012;Nwanzu & Babalola, 2019).…”
Section: Theoretical and Practical Implicationssupporting
confidence: 67%
“…We provide evidence that the relationship between psychological capital and internal learning is mediated by the perceived team structure. This confirms that one of the distinctive features of psychological capital, and one that has an important practical contribution to make, is its openness to change and development (Choi & Lee, 2014;Han, Brooks, Kakabadse, Peng, & Zhu, 2012;Nwanzu & Babalola, 2019).…”
Section: Theoretical and Practical Implicationssupporting
confidence: 67%
“…Self-efficacy reflects individual's perception of his/her ability and necessary skills to perform a specific task to control or manage issues (Bandura, 1977(Bandura, , 1986(Bandura, , 2001). Nwanzu and Babalola (2019) stated that self-efficacy shows a belief in one's abilities to perform a specific task. It is believing and seeing oneself as being able to deal with the challenges of life.…”
Section: The Role Of Entrepreneurial Self-efficacymentioning
confidence: 99%
“…Optimism efficiently and professionally diminishes adverse behavioral responses (Drugan, 2000;Maier & Watkins, 2000;Peterson, 2000;Peterson & Bossio, 1991;Seligman, 1991;Seligman, Martin, & Csikszentmihalyi, 2000), moreover, optimists tend to assume good things occur to them, shows more optimistic attitudes i.e. life satisfaction, acceptance of organizational change, creative performance (Bouzari & Karatepe, 2020;Jaworski et al, 2020;Nwanzu & Babalola, 2019;Seo & Lim, 2019;Siniver & Yaniv, 2019) thus, optimism tends to be an important source of positive change that also observed as a psychological aspect to overcome the physical and psychological health matters (Basten-Günther, Peters, & Lautenbacher, 2019). Additionally, Xanthopoulou et al (2009) theorize that optimism affects employees' efficiency at the workplace and the level of optimism helps the peoples to understand, shape and respond to the environment (Judge, Locke, & Durham, 1997;Xanthopoulou et al, 2009).…”
Section: Employee Optimism As Moderatormentioning
confidence: 99%
“…It was observed that optimism negatively predicted burnout, and optimistic individuals much better tackle OBT i.e. emotional exhaustion, fatigue and cynicism, due to their strong confidence in self-efficacy and well-being that resulted to high-level of satisfaction (Seo & Lim, 2019;Vizoso, Arias-Gundín, & Rodríguez, 2019) and these individuals also helpful during the implementation of the change process in organizations (Nwanzu & Babalola, 2019). Also, Kobasa (1979), observed hardiness as a construct of three mechanisms and presented the notion as control, commitment, and challenge.…”
Section: Introductionmentioning
confidence: 96%